Integration of IR‐808 Sensitized Upconversion Nanostructure and MoS2 Nanosheet for 808 nm NIR Light Triggered Phototherapy and Bioimaging. Issue 36 (24th July 2017) - Xu, Jiating; Gulzar, Arif; Liu, Yuhui; Bi, Huiting; Gai, Shili; Liu, Bin; Yang, Dan; He, Fei; Yang, Piaoping
Abstract : Near infrared (NIR) light triggered phototherapy including photothermal therapy (PTT) and photodynamic therapy (PDT) affords superior outcome in cancer treatment. However, the reactive oxygen species (ROS) generated by NIR‐excited upconversion nanostructure is limited by the feeble upconverted light which cannot activate PDT agents efficiently. Here, an IR‐808 dye sensitized upconversion nanoparticle (UCNP) with a chlorin e6 (Ce6)‐functionalized silica layer is developed for PDT agent. The two booster effectors (dye‐sensitization and core–shell enhancement) synergistically amplify the upconversion efficiency, therefore achieving superbright visible emission under low 808 nm light excitation. The markedly amplified red light subsequently triggers the photosensitizer (Ce6) to produce large amount of ROS for efficient PDT. After the silica is endowed with positive surface, these PDT nanoparticles can be easily grafted on MoS2 nanosheet. As the optimal laser wavelength of UCNPs is consistent with that of MoS2 nanosheet for PTT, the invented nanoplatform generates both abundant ROS and local hyperthermia upon a single 808 nm laser irradiation. Both the in vitro and in vivo assays validate that the innovated nanostructure presents excellent cancer cell inhibition effectiveness by taking advantages of the synergistic PTT and PDT, simultaneously, posing trimodal (upconversion luminescence/computed tomography (CT)/magnetic resonance imaging (MRI) imaging capability. Abstract : A novel nanostructure with photodynamic therapy (PDT) and photothermal therapy (PTT) effect is first synthesized by grafting highly efficient photodynamic upconversion nanoparticles on a MoS2 nanosheet, which exhibits high tumor inhibition efficacy due to a synergetic PDT and PTT mediated by a biocompatible near infrared laser, and the therapeutic process can be visualized by trimodal (upconversion luminescence/computed tomography (CT)/magnetic resonance imaging (MRI) imaging.